PENGARUH KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP SEMANGAT KERJA KARYAWAN DI DAZZLE ACCESSORIES YOGYAKARTA - Hesty Wulandari Hesty (Program Studi Manajemen Fakultas Ekonomi UST, 2020)
The purpose thisof research is to know the influence of compensation and cultural organization of employees at Dazzle Accessories Yogyakarta. The population of this research is permanent employees at Dazzle Accessories Yogyakarta with a total of 97 employees. Sampling techniques are saturated samples by taking all samples of 97 employees. Method of collecting data with questionnaires. Results showed that partial compensation did not significantly affect the morale of work. While organizational culture has a significant impact on employee morale.